Viral hepatitis in Germany: poor vaccination coverage and little knowledge about transmission in target groups - Bocter Nikolaus; Bremer Viviane; Radun Doris; Schenkel Karl; Hamouda Osamah (BMC, 2008)
Abstract Background In Germany, vaccination against hepatitis B is recommended for infants, children and adolescents since 1995 and for specific target groups since 1982. Little is known about knowledge about viral hepatitis and attitudes toward hepatitis B vaccination-factors likely to influence vaccine uptake. Methods In order to estimate vaccination coverage in adult target groups and in the overall adult population and to assess knowledge and attitudes, we conducted a nationwide cross-sectional telephone survey among 412 persons in November 2004. We defined participants as being vaccinated if they reported at least one previous vaccination against hepatitis B. Results Vaccination coverage (vc) standardised for age, sex and residence was 29.6% in the general population and 58.2% in target groups for hepatitis B vaccination. Particular gaps in vaccine coverage were detected among health care workers (vc: 69.5%) and chronically ill persons (vc: 22.0%). Knowledge on risk factors and transmission was far below expectations, whereas the acceptance of vaccination in the majority of the population (79.0%) was good. Conclusion We conclude that educational measures could lead to a higher vaccination uptake in adult target groups.